“Crisis”, “Revolution”, “Civil War” as Components of the Concept of Scientific Reproduction of the Social Progress of Ukraine in 1917–1920 - Солдатенко, Валерій Федорович (Київський національний університет імені Тараса Шевченка, 2024)
The article seeks to elucidate the logical interconnections, interdependencies, and reciprocal influences of significant social phenomena during one of the most pivotal periods in Ukrainian history. Even a general framework for understanding these phenomena can facilitate a constructive crystallization of approaches, enhance methodological consistency in research practices, and foster a clearer comprehension of events from a century ago, which are currently subjected to diverse, often conflicting or unconvincing interpretations within historiography and political science. By rationalizing the interplay and clarifying distinctions among the theoretical constructs of «crisis», «revolution», and «civil war» through the lens of the historical context from 1917–1920, this analysis presents opportunities for a more precise and realistic depiction of intricate social trends and processes. Specifically, this methodical examination reveals that a singular, linear model depicting progression along an ascending trajectory—moving «from the smaller to the larger»—is inadequate. Instead, it necessitates a more adaptable and dialectical approach; it becomes evident that not only can political crises precipitate revolutions—which may subsequently incite civil wars—but civil wars themselves can initiate a «reverse reversal», triggering political crises. Moreover, the ramifications of civil wars significantly alter the developmental trajectory of revolutions and influence choices regarding pathways for social development.

У статті здійснено спробу прослідкувати логічні взаємозв’язки, взаємозалежності, взаємовпливи ключових суспільних феноменів одного з найважливіших, переламних, доленосних періодів вітчизняної історії. Навіть найзагальніша їх структуризація може сприяти позитивній кристалізації підходів, досягненню більшої системності у застосуванні методологічних і методичних засобів освоєння, творчого осмислення подій столітньої давнини, які в наявній на сьогодні історіографії, політологічних студіях отримують відмінні, нерідко суперечливі, або непереконливі тлумачення й оцінки. Раціоналізація поєднання, рівно як і з’ясування відмінностей теоретичних категорій «криза», «революція», «громадянська війна» на ґрунті конкретно-історичного досвіду 1917–1920 рр. створює додаткові можливості для точнішого, реалістичнішого відтворення надскладних суспільних тенденцій і процесів. Здійснений у такий спосіб аналіз, зокрема, свідчить: однолінійна, однопланова умовна схема руху по висхідній логічній лінії «від меншого до більшого» (масштабнішого) виявляється недостатньою, вимагає гнучкішого, діалектичнішого застосування, оскільки з’ясовується, що не лише політичні кризи здатні призводити до революцій, які, своєю чергою породжують громадянські війни, а й останні, здійснюючи «зворотній реверс», призводять до політичних криз, а наслідки громадянських війн виявляють себе в істотній корекції вектору розвитку революцій, вибору траєкторій суспільного розвитку.
«Криза», «революція», «громадянська війна» як складові концепту наукового відтворення суспільного поступу України в 1917–1920 рр.
Keywords: crisis; Ukrainian revolution; social aspects; civil war; intervention; occupation; insurgency; «reds» and «whites»; криза; Українська революція; соціальні аспекти; громадянська війна; інтервенція; окупація; повстанство; червоні й білі